A Pragmatic Review of COVID-19 Management: Therapeutic Approaches, Challenges, and Recommendations - Revathi K; Madhumitha. N; Swathi T; Linisha.N.M; Subha. S. C (The Bioscan, 2025)
The coronavirus disease 2019 (COVID-19), caused by the novel RNA virus SARS-CoV-2, was declared a global pandemic on 11 March 2020. Its rapid worldwide transmission highlighted the urgent need for effective clinical management strategies. Patients with inflammatory and immunological disorders undergoing systemic immunotherapy face an increased risk of infection and adverse outcomes. This review critically examines current therapeutic approaches, including the use of steroids, remdesivir, oxygen therapy, and vaccination, alongside an assessment of unproven treatments such as ivermectin and hydroxychloroquine. Emphasis is placed on pragmatic home-based care for mild to moderate cases to reduce the burden on overstrained healthcare systems. Furthermore, challenges related to misinformation, resource shortages, and inconsistent policy implementation are discussed. The findings suggest that systemic immunotherapy may be continued in selected patients with careful monitoring, while broader strategies such as vaccination, early triage, and community-level interventions remain central to effective pandemic control.